Dissecting Gene Repression: Not Just Location, Location, Location. Issue 8 (August 2019) - Sexton, Tom
Abstract : Large heterochromatic domains are found tethered to the lamina. But, is this nuclear environment repressive per se, or just the 'ground state' of inactive chromatin? Elegant studies from the van Steensel group (Leemans et al., Cell, 2019) recently demonstrated that the lamina is indeed repressive, but that intrinsic promoter properties also dictate gene activity.